2018
DOI: 10.1177/1559325818812188
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin and Idebenone Ameliorate Oxidative Stress, Inflammation, DNA damage, and Apoptosis Induced by Titanium Dioxide Nanoparticles in Rat Liver

Abstract: Titanium dioxide nanoparticles (TiO2-NPs) are extensively used in a wide range of applications; however, many reports have investigated their nanotoxicological effect at the molecular level either in vitro or in vivo systems. The defensive roles of quercetin (Qur) or idebenone (Id) against the hepatotoxicity induced by TiO2-NPs were evaluated in the current study. The results showed that the coadministration of Qur or Id to rats intoxicated with TiO2-NPs markedly ameliorated the elevation in hepatic malondiald… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 41 publications
0
20
0
2
Order By: Relevance
“…The current study used idebenone at a dose of 200 mg/kg that previously ameliorated oxidative stress, pro-inflammatory cytokines and DNA damage in a titanium-dioxide-induced hepatotoxicity model [41], and also improved cardiac function [42]. Since administration of idebenone with food is known to increase its bioavailability by 5 to 7 times [43], idebenone was administered with chow pellets in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The current study used idebenone at a dose of 200 mg/kg that previously ameliorated oxidative stress, pro-inflammatory cytokines and DNA damage in a titanium-dioxide-induced hepatotoxicity model [41], and also improved cardiac function [42]. Since administration of idebenone with food is known to increase its bioavailability by 5 to 7 times [43], idebenone was administered with chow pellets in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin (3,3,4,5,7-pentahydroxyflavone), a natural flavonoid compound found in vegetables and fruits, has a prominent antioxidant, and anti-inflammatory activities [10]. Quercetin was found to downregulate the serum levels of immunoinflammatory mediators, TNF-α, IL-6 and Creactive protein, protecting liver in atitanium dioxide nanoparticles induced liver injury rat model [11]. Additionally, quercetin affords antifibrotic effect by preventing TGF-β signaling pathways and fibroblast activation in carbon tetrachloride and thioacetamide induced hepatic toxicity in rats [6].…”
Section: Introductionmentioning
confidence: 99%
“…35 Further biochemical studies suggested that DNA protective role of quercetin was based on enhancement of antioxidant defense system reduced glutathione (GSH) level, catalase (CAT) and glutathione peroxidase (GPx) activities with reduction in oxidative stress parameters such as thiobarbituric acidreacting substance (TBARS), by deoperoxides and NO levels. 36,37 Kaempferol was shown to exhibit moderate antimutagenic effect. Glycosilation at C-3 showed no significant influence on glycosylated flavonoid antimutagenic activity.…”
Section: Discussionmentioning
confidence: 99%